UBR4 deficiency causes male sterility and testis abnormal in Drosophila - Xie, Shi-Ming; Lai, Jia-Xuan; Liu, Chu-Qiao; Zhang, Xi-Xing; Lin, Yong-Miao; Lan, Qi-Wen; Hong, De-Yao; Chen, Xiao-Chuan; Qiao, Jing-Da; Mao, Yu-Ling (Frontiers in Endocrinology, 2023)
It has been established that UBR4 encodes E3 ubiquitin ligase, which determines the specificity of substrate binding during protein ubiquitination and has been associated with various functions of the nervous system but not the reproductive system. Herein, we explored the role of UBR4 on fertility with a Drosophila model. Different Ubr4 knockdown flies were established using the UAS/GAL4 activating sequence system. Fertility, hatchability, and testis morphology were studied, and bioinformatics analyses were conducted. Our results indicated that UBR4 deficiency could induce male sterility and influent egg hatchability in Drosophila. We found that UBR4 deficiency affected the testis during morphological analysis. Proteomics analysis indicated 188 upregulated proteins and 175 downregulated proteins in the testis of Ubr4 knockdown flies. Gene Ontology analysis revealed significant upregulation of CG11598 and Sfp65A, and downregulation of Pelota in Ubr4 knockdown flies. These proteins were involved in the biometabolic or reproductive process in Drosophila. These regulated proteins are important in testis generation and sperm storage promotion. Bioinformatics analysis verified that UBR4 was low expressed in cryptorchidism patients, which further supported the important role of UBR4 in male fertility. Overall, our findings suggest that UBR4 deficiency could promote male infertility and may be involved in the protein modification of UBR4 by upregulating Sfp65A and CG11598, whereas downregulating Pelota protein expression.